The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/molecules26133866
|View full text |Cite
|
Sign up to set email alerts
|

Pros and Cons of the Cannabinoid System in Cancer: Focus on Hematological Malignancies

Abstract: The endocannabinoid system (ECS) is a composite cell-signaling system that allows endogenous cannabinoid ligands to control cell functions through the interaction with cannabinoid receptors. Modifications of the ECS might contribute to the pathogenesis of different diseases, including cancers. However, the use of these compounds as antitumor agents remains debatable. Pre-clinical experimental studies have shown that cannabinoids (CBs) might be effective for the treatment of hematological malignancies, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 205 publications
2
4
0
Order By: Relevance
“…The side effects of cannabinoids are mainly caused by the activation of CB1, suggesting that treatments should aim to selectively avoid CB1 activation and target CB2 receptors. 29 In the present study, we verified the anti-tumor effect of CB2 overexpression in the development of BC, and also verified the anti-tumor effect of the CB2-specific agonist JWH-015 in BC. CCK-8 and colony-forming experiments verified that CB2 overexpression and treatment with a CB2-specific agonist inhibited the growth of BC cells, while flow cytometry and TUNEL staining showed that CB2 promoted BC cell apoptosis.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The side effects of cannabinoids are mainly caused by the activation of CB1, suggesting that treatments should aim to selectively avoid CB1 activation and target CB2 receptors. 29 In the present study, we verified the anti-tumor effect of CB2 overexpression in the development of BC, and also verified the anti-tumor effect of the CB2-specific agonist JWH-015 in BC. CCK-8 and colony-forming experiments verified that CB2 overexpression and treatment with a CB2-specific agonist inhibited the growth of BC cells, while flow cytometry and TUNEL staining showed that CB2 promoted BC cell apoptosis.…”
Section: Discussionsupporting
confidence: 78%
“…However, using the cannabinoid system to treat cancer is associated with mental side effects, such as dizziness, fatigue, and palpitations, 27,28 indicating the need to adopt different strategies to reduce the side effects of cannabinoids. The side effects of cannabinoids are mainly caused by the activation of CB1, suggesting that treatments should aim to selectively avoid CB1 activation and target CB2 receptors 29 . In the present study, we verified the anti‐tumor effect of CB2 overexpression in the development of BC, and also verified the anti‐tumor effect of the CB2 ‐specific agonist JWH‐015 in BC.…”
Section: Discussionsupporting
confidence: 76%
“…WM may present with symptoms of hyperviscosity and may also present with weight loss, neuropathy, and fatigue, all of which may be alleviated by cannabis use. In hematologic malignancies, cannabinoids may activate pathways of programmed cell death and may promote response to chemotherapy [ 5 - 6 ]. In HPV+ SCC in particular, cannabinoids activate the p38 MAPK pathway and stimulate HPV+ disease progression in the head and neck [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…CBD inhibits the breakdown of anandamide, thereby counteracting the effect of THC as a cannabinoid receptor agonist. Finally, THC and CBD may affect and inhibit a number of transporters and enzymes involved in the distribution and metabolism of drug compounds [ 9 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ].…”
Section: Pharmacognostic and Pharmacological Backgroundmentioning
confidence: 99%